On the low-temperature anomalies in the thermal conductivity of plastically deformed crystals due to phonon-kink scattering - Ostaay, J.A.M. van; Mukhin, S.I.; Mezhov-Deglin, L.P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
Previous experimental studies of the thermal conductivity of plastically deformed lead crystals in the superconducting state have shown strong anomalies in the thermal conductivity. Similar effects were also found for the thermal conductivity of bent 4He samples. Until now, a theoretical explanation for these results was missing. In this paper we will introduce the process of phonon–kink scattering and show that it qualitatively explains the anomalies that experiments had found.